Impact of gastrointestinal symptoms and psychological distress on quality of life in systemic sclerosis: a cross-sectional study - Claudia Barber; Ariadna Aguilar; Alfredo Guillén-Del-Castillo; Luis Gerardo Alcala-Gonzalez; Claudia Codina; Antonio Marin Garcia; Carolina Malagelada; Carmen P Simeon-Aznar (BMJ Open)
Background Systemic sclerosis (SSc) is a chronic autoimmune disease characterised by microvascular damage and fibrosis. Mortality in patients with SSc has significantly decreased. Consequently, patients with SSc have longer life expectancy, and health-related quality of life (HrQoL) has become more relevant in the comprehensive management of the disease.Objective To evaluate the impact between gastrointestinal (GI) symptom burden and psychological well-being on HrQoL in patients with SSc.Design Nested cross-sectional study conducted between January and July 2022.Participants A single-centre cohort of 166 patients with SSc, including 103 (55%) with limited cutaneous SSc, 43 (24%) with diffuse SSc and 37 (21%) with sine-sclerosis SSc.Main measures GI symptom burden was assessed using the University of California Los Angeles Scleroderma Clinical Trial Consortium gastrointestinal tract 2.0 (UCLA SCTC GIT 2.0) questionnaire, psychological well-being was measured with the Hospital Anxiety and Depression Scale (HADS), and HrQoL was evaluated using the Short Form 36 (SF-36) questionnaire. Demographic, clinical and immunological data were collected from a prospectively maintained database.Key results Patients with moderate to severe GI symptoms (UCLA SCTC GIT 2.0 score >0.5, n=95, 57%) reported decreased HrQoL in all subdomains except vitality by SF-36, and higher anxiety and depression scores by HADS (all p<0.05). The severity of GI symptom burden and depression were independently associated with a decline in the physical component of QoL (β=−0.273 and β=−0.411, respectively, p<0.01 for both). Only the severity of depression and anxiety (β=−0.482 and β=−0.213, respectively, p<0.05), but not GI symptom burden, were independently associated with a decline in the mental component of QoL.Conclusions Our data suggest that in patients with SSc, GI and psychological burden negatively influence quality of life independently, highlighting the need for a holistic approach to patient’s care.